Dependence of Single‐Wall Carbon Nanotube Alignment on the Filter Membrane Interface in Slow Vacuum Filtration. Issue 11 (22nd January 2022) - Walker, Joshua S.; Macdermid, Zia J.; Fagan, Jeffrey A.; Kolmakov, Andrei; Biacchi, Adam J.; Searles, Thomas A.; Walker, Angela R. Hight; Rice, William D.
Abstract: The recent introduction of slow vacuum filtration (SVF) technology has shown great promise for reproducibly creating high‐quality, large‐area aligned films of single‐wall carbon nanotubes (SWCNTs) from solution‐based dispersions. Despite clear advantages over other SWCNT alignment techniques, SVF remains in the developmental stages due to a lack of an agreed‐upon alignment mechanism, a hurdle which hinders SVF optimization. In this work, the filter membrane surface is modified to show how the resulting SWCNT nematic order can be significantly enhanced. It is observed that directional mechanical grooving on filter membranes does not play a significant role in SWCNT alignment, despite the tendency for nanotubes to follow the groove direction. Chemical treatments to the filter membrane are shown to increase SWCNT alignment by nearly 1/3. These findings suggest that membrane surface structure acts to create a directional flow along the filter membrane surface that can produce global SWCNT alignment during SVF, rather serving as an alignment template. Abstract : Aligned single‐wall carbon nanotube (SWCNT) films using the slow vacuum filtration (SVF) technique follow the unintentional grooving of the as‐received filter membrane on which they are made, suggesting templating is the dominant SVF alignment mechanism. In this work, it is shown that both the SWCNT nematic order and the grooving‐to‐SWCNT angle, θshift, increase when the membrane is mechanically and chemically modified.